Superhydrophobic sand mulch and date palm biochar boost growth of Moringa oleifera in sandy soils via enhanced irrigation and nutrient use efficiency - Odokonyero, Kennedy; Vernooij, Bob; Albar, Batool; Exposito, Lisa Oki; Alsamdani, Aishah; Haider, Amin Akhtar Ghulam; Musskopf, Nayara Vivian Huve; Kharbatia, Najeh; Gallo, Adair; Mishra, Himanshu (Frontiers in Plant Science, 2024)
It is desirable to rehabilitate desert ecosystems with a selection of native plant species that render ecosystem services and yield natural products for creating a high-value industry, e.g., pharmaceuticals or cosmetics. However, plant growth under arid and hyper-arid conditions, such as in the Arabian Peninsula, is constrained by heat, freshwater scarcity, and alkaline sandy soils with low nutrient and water holding capacity. Therefore, it is imperative to develop nature-based sustainable technologies to improve arid soil conditions, as well as increase irrigation and nutrient-use efficiency. Here, we report on a study evaluating the effects of two complementary soil amendment technologies, namely Superhydrophobic sand (SHS) mulch and engineered biochar (EB) on the growth of Moringa oleifera plants. Effects of SHS (1cm-thick), EB (2% w/w), and SHS+EB treatments were tracked in greenhouse plants under normal (N, 100% field capacity) and reduced (R, 50% of N) irrigation scenarios for over 150 days, where EB treatments were pre-loaded with nutrients and remaining treatments received traditional NPK fertilizer. Significant benefits of the SHS, EB, and SHS+EB treatments were found in terms of increased plant height, trunk diameter, leaf area, leaf chlorophyll content index, stomatal conductance, and shoot and root biomass, in comparison with the controls. Evaporation water savings due to SHS mulching significantly enhanced transpiration under N and R. Similarly, EB and SHS+EB treated plants experienced higher transpiration than in the control plants under N and R (p < 0.05). In response to water stress due to excessive evaporation, metabolomics analysis showed a higher accumulation of amino acids in control plants than other treatments under both irrigation regimes. Meanwhile, a higher abundance of sugars (i.e., D-Mannose, D-Fructose, glucose) and organic acid (i.e., malic acid) was observed in SHS and EB-treatments for Variable Importance in Projection (VIP) scores >1.0 (i.e., the scores considered of significance in contributing to the differences between treatment groups). The results show the synergistic benefits of SHS and EB technologies for addressing the challenges of water scarcity and nutrient limitation in arid regions, which could underscore the success and sustainability of agriculture and greening efforts in such regions.